A method for preparing degradable breathable antibacterial gloves

By using components such as nitrile rubber modified polylactic acid and modified antibacterial filler, the problem that existing gloves are difficult to have both degradability, breathability and antibacterial properties, and the green degradability and long-lasting antibacterial properties of gloves are achieved.

CN119505552BActive Publication Date: 2025-04-25SHANDONG INTE MEDICAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510065676.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-25
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Existing protective gloves are difficult to have both degradability, breathability and antibacterial properties, and have poor antibacterial performance.

Method used

Nitrile rubber modified polylactic acid is used as the main matrix, combined with modified antibacterial filler and foaming agent, the partial degradation function and breathable performance of the material are optimized through the introduction of polylactic acid, and at the same time, the antibacterial components in the antibacterial filler form a long-acting antibacterial barrier.

Benefits of technology

The gloves are controlled degradable, durable antibacterial and good breathability are achieved, and the gloves are environmentally friendly and safe.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention relates to the technical field of preparation of antibacterial gloves, and in particular to a method for preparing degradable breathable antibacterial gloves. The emulsion formula of the degradable breathable antibacterial gloves is, by weight, 100 parts of nitrile rubber modified polylactic acid, 5-10 parts of modified antibacterial filler, 1-3 parts of anti-aging agent, 0.5-3 parts of vulcanizing agent, 0.3-2 parts of vulcanization accelerator and 0.5-1 parts of foaming agent. The present invention prepares a kind of gloves with controllable degradability, lasting antibacterial property and good air permeability by compounding components such as nitrile rubber modified polylactic acid and modified antibacterial filler through a polymer compound composition system, and realizes the synergistic antibacterial of modified antibacterial filler based on the covalent bonding of silica loaded with antibacterial groups and modified chitosan, thereby improving the antibacterial property of the gloves.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of antibacterial gloves preparation, and in particular to a method for preparing degradable breathable antibacterial gloves. Background Art

[0002] With the enhancement of environmental protection awareness and the improvement of medical and health requirements, the use of protective gloves has shown a rapid growth trend. At present, the commonly used protective gloves on the market are mainly made of traditional polymer materials such as nitrile rubber, natural latex, and PVC. Although polymer compound compositions have been widely studied in the field of glove preparation in recent years, there are still problems such as poor component compatibility and unsatisfactory performance synergy. As an important polymer compound, nitrile rubber is currently a common material for the preparation of protective gloves. Although it has excellent mechanical properties and protective properties, it has significant defects such as non-degradability and poor air permeability. Discarded gloves after a large number of uses are difficult to degrade, causing serious environmental pollution problems; at the same time, the lack of air permeability of traditional gloves leads to discomfort such as stuffiness and humidity in the hands when worn for a long time, and it is easy to breed bacteria in high temperature and high humidity environments, increasing the risk of cross infection.

[0003] The existing patent CN2020105674650 provides a degradable nitrile medical glove and a preparation method thereof. The principle is to add a biodegradable acrylonitrile grafted starch component that is compatible with nitrile latex. The emulsion formula includes nitrile latex, acrylonitrile grafted starch, antioxidant, sulfur, zinc oxide, accelerator, and potassium hydroxide. The gloves prepared by the above technical solution have a tensile strength of up to 21MPa, an elongation at break of up to 521%, and a degradation rate of up to 60%. However, the gloves prepared by the above technical solution have poor antibacterial properties. After contacting the skin, pathogens, body fluids or pollutants, surface bacteria tend to proliferate rapidly, increasing the risk of cross infection; even if the surface is coated with antibacterial coating in the subsequent process, conventional antibacterial coatings (such as silver ions, quaternary ammonium salt coatings) are easy to fall off due to friction, resulting in a short antibacterial action time, or even complete failure of antibacterial properties after long-term storage. Summary of the invention

[0004] In view of this, the present invention proposes a method for preparing degradable, breathable and antibacterial gloves to solve the problem in the prior art that protective gloves are difficult to have both degradability, breathability and antibacterial properties, and the durability of antibacterial performance is poor.

[0005] The technical solution of the present invention is achieved as follows: The present invention provides a degradable breathable antibacterial glove, and the emulsion formula of the degradable breathable antibacterial glove is as follows, by weight: 100 parts of nitrile rubber modified polylactic acid, 5-10 parts of modified antibacterial filler, 1-3 parts of anti-aging agent, 0.5-3 parts of vulcanizing agent, 0.3-2 parts of vulcanization accelerator and 0.5-1 parts of foaming agent.

[0006] In the present invention, the graft modification of nitrile rubber and polylactic acid not only maintains the excellent mechanical properties and processing properties of nitrile rubber, but also realizes the partial degradation function of the material through the introduction of polylactic acid; in addition, the introduction of polylactic acid molecular segments optimizes the air permeability of the gloves. The foaming agent further improves the air permeability of the gloves by forming a fine and uniform pore structure in the material. The anti-aging agent can effectively prevent the material from oxidative aging and thermal aging during use and storage. The antibacterial component loaded by the modified antibacterial filler can form a long-lasting antibacterial barrier and improve the antibacterial performance of the gloves.

[0007] On the basis of the above technical solution, preferably, the preparation method of the modified antibacterial filler is as follows:

[0008] S1, dispersing the amino mesoporous silica in THF, adding triethylamine and oleyl chloride under nitrogen protection, stirring and reacting to obtain amidated silica;

[0009] S2, dispersing the amidated silica in DMF, adding 2-mercaptobenzimidazole carboxylic acid and a photoinitiator, and subjecting to ultraviolet irradiation reaction to obtain modified silica;

[0010] S3, dissolving chitosan in 1-2% v / v acetic acid solution, adding ammonium persulfate, and then adding acrylonitrile monomer to react to obtain acrylonitrile-grafted chitosan;

[0011] S4, acrylonitrile grafted chitosan was dispersed in a methanol / THF mixed solvent, sodium borohydride was added under ice bath condition, the temperature was raised to 25-30°C and the reaction was continued for 2-3h, and dilute hydrochloric acid was immediately added after the reaction was completed for neutralization to obtain modified chitosan;

[0012] S5. Disperse the modified silica in DMF, add EDC and NHS, activate for 20-30 minutes, add the modified chitosan solution, react at 25-30° C. for 16-24 hours to obtain a modified antibacterial filler.

[0013] In the present invention, in step S1, oleoyl chloride is used to react with the surface amino group of the amino-modified mesoporous silica to undergo an amidation reaction, and a double bond is introduced to provide an active site for subsequent reactions; in step S2, a thiol-ene click chemistry reaction is carried out with 2-mercaptobenzimidazole carboxylic acid via the double bond to introduce a benzimidazole group with antibacterial activity. The introduction of benzimidazole not only gives the silica particles an antibacterial function, but its carboxyl group can also serve as an active point for connecting with modified chitosan in subsequent steps; in steps S3-S4, the chitosan is effectively initiated and polymerized with acrylonitrile to form a The grafted copolymer is then partially reduced by sodium borohydride to increase the active primary amine reaction sites on the chitosan molecule; in step S5, the modified antibacterial filler is obtained by amidation coupling between the carboxyl groups on the surface of the modified silica and the amino groups on the modified chitosan, and the residual cyano groups on the modified chitosan form strong polar interactions with the cyano groups in the nitrile rubber, thereby significantly improving the compatibility of the modified antibacterial filler with the matrix; at the same time, the modified chitosan is firmly bonded to the surface of the modified silica through covalent bonds, thereby improving the stability of the modified antibacterial filler.

[0014] On the basis of the above technical solution, preferably, the preparation method of the amino mesoporous silica is as follows:

[0015] S11, adding hexadecyltrimethylammonium bromide to a mixed solution of ammonia water, deionized water and ethanol, stirring evenly, then adding tetraethyl orthosilicate and aminosilane coupling agent, reacting for 4-5h, to obtain amino silica;

[0016] S12. Place the amino-containing silica in a crucible and calcine in a muffle furnace at a temperature of 500-550° C. for 5-6 hours to obtain amino-containing mesoporous silica.

[0017] Mesoporous silica, as a core carrier, can compensate for the reduction in toughness caused by the introduction of polylactic acid; at the same time, the porous structure of mesoporous silica not only provides abundant surface active sites, but also can serve as a storage and sustained-release carrier for antibacterial molecules and other functional substances.

[0018] On the basis of the above technical scheme, preferably, in step S11, the mass volume ratio of hexadecyltrimethylammonium bromide, ammonia water, deionized water, anhydrous ethanol, tetraethyl orthosilicate and aminosilane coupling agent is 0.5-1.0g:1-1.5ml:60-80ml:40-60ml:0.5-1.2ml:0.4-0.6ml, and the aminosilane coupling agent is 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane.

[0019] On the basis of the above technical scheme, preferably, in step S1, the mass ratio of amino silicon dioxide, oleoyl chloride and triethylamine is 1:2-3:1, the reaction temperature is 50-60° C., and the reaction time is 6-8 h.

[0020] On the basis of the above technical scheme, preferably, in step S2, the mass ratio of amidated silica, 2-mercaptobenzimidazole carboxylic acid and photoinitiator is 1:1.5-2:0.2-0.4, the reaction temperature is 40-50°C, and the reaction time is 1-2h; and the photoinitiator is diphenylacetone.

[0021] Based on the above technical solution, preferably, in step S3, the mass ratio of chitosan to acrylonitrile is 1:2.5-3, the amount of ammonium persulfate added is 0.2-0.5% of the total mass of chitosan and acrylonitrile; the reaction temperature is 60-70°C, and the reaction time is 4-6h.

[0022] On the basis of the above technical scheme, preferably, in step S4, the mass ratio of acrylonitrile grafted chitosan and sodium borohydride is 1:0.5-0.8; in step S5, the mass ratio of modified silica, modified chitosan, EDC and NHS is 1:1.5-1.8:1.2:0.5, and the mass percentage of chitosan in the modified chitosan solution is 1-2%.

[0023] On the basis of the above technical scheme, preferably, the anti-aging agent is 2,6-di-tert-butyl-p-cresol, the vulcanizing agent is sulfur and zinc oxide, the vulcanization accelerator is any one or more of diphenylguanidine, diethylthiourea, thiuram and 2-mercaptobenzothiazole, and the foaming agent is sodium fluorosilicate.

[0024] The present invention provides a method for preparing a degradable breathable antibacterial glove as described above, comprising the following steps: preparing an impregnating latex according to the emulsion formula of the degradable breathable antibacterial glove, adjusting the amount of water used, and maintaining the solid content of the impregnating liquid at 20-40%; impregnating a hand mold in the impregnating latex, and obtaining the degradable breathable antibacterial glove by heating, vulcanizing, and demolding.

[0025] The method for preparing the degradable breathable antibacterial gloves of the present invention has the following beneficial effects compared with the prior art:

[0026] (1) A glove with controllable degradability, durable antibacterial properties and good breathability was prepared by compounding components such as nitrile rubber modified polylactic acid and modified antibacterial filler. The degradable polylactic acid was used as the main matrix, combined with the flexibility and fatigue resistance of nitrile rubber, to balance the mechanical properties and environmental friendliness, thereby achieving green degradability and breathability of the gloves. The modified antibacterial filler was synergistically antibacterial based on the covalent bonding of silica loaded with antibacterial groups and modified chitosan, thereby improving the antibacterial properties of the gloves.

[0027] (2) In the modified antibacterial filler, benzimidazole interferes with DNA replication and transcription through intercalation with bacterial DNA, thus fundamentally inhibiting bacterial proliferation; at the same time, the modified chitosan further enhances the antibacterial activity of the material by interacting destructively with the bacterial cell wall. The synergistic effect of the two antibacterial mechanisms not only improves the antibacterial efficiency, but also reduces the adaptability of bacteria in the antibacterial environment, slowing down the generation of drug-resistant strains. The porous structure of mesoporous silica provides a loading and release path for the antibacterial components, effectively ensuring the long-term effect of the antibacterial components and improving the durability of the antibacterial performance; at the same time, mesoporous silica, as an inorganic reinforcing filler, can improve the toughness of the composite material, and the residual polyacrylonitrile segments on the modified chitosan further enhance the strength of the interface bonding, giving the material better mechanical properties. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] In this embodiment, chitosan was purchased from Shandong Haiyihua Biotechnology Co., Ltd., with a serial number of 618-480-0, a deacetylation rate of ≥85%, and a viscosity of ≤100 mPa.s.

[0030] In this embodiment, the preparation method of nitrile rubber modified polylactic acid is as follows:

[0031] Add polylactic acid to acetone, stir until dissolved at 50°C and 300r / min, cool to room temperature, add amino-terminated liquid nitrile rubber and 4-dimethylaminopyridine, the mass ratio of polylactic acid, acetone, amino-terminated liquid nitrile rubber and 4-dimethylaminopyridine is 100:600:50:0.5, react at 30°C for 5h, after the reaction, remove acetone by rotary evaporation to obtain a crude reaction product, add ethanol 10 times the mass of the crude reaction product to the crude reaction product for washing, filter, repeat washing and filtering three times, and then dry in a vacuum drying oven at 80°C for 10h to obtain nitrile rubber modified polylactic acid.

[0032] Example 1

[0033] This embodiment provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0034] (1) Add 8 g of hexadecyltrimethylammonium bromide to a mixed solution of 12.5 ml of ammonia water (mass fraction of 26%), 700 ml of deionized water and 500 ml of ethanol, stir evenly at 25°C, then add 8 ml of ethyl orthosilicate and 5 ml of 3-aminopropyltrimethoxysilane, react at 25°C for 4.5 h, and after the reaction is completed, wash with deionized water and anhydrous ethanol in turn to obtain amino silica; place the amino silica in a crucible and calcine in a muffle furnace at a calcination temperature of 520°C for 5.5 h. After the calcination is completed, cool to 25°C with the furnace to obtain amino mesoporous silica;

[0035] (2) Disperse 10 g of amino mesoporous silica in 100 ml of THF, and ultrasonically disperse for 30 min. Add 10 g of triethylamine under nitrogen protection and stir evenly. Then, slowly drop 25 g of oleoyl chloride in an ice bath. After the dropwise addition, heat to 55 °C and continue stirring for 7 h. After the reaction, filter, wash and dry to obtain amidated silica.

[0036] (3) Disperse 10 g of amidated silica in 100 ml of DMF, perform ultrasonic dispersion for 30 min, add 18 g of 2-mercaptobenzimidazole carboxylic acid and 3 g of benzophenone, and irradiate the mixture with an ultraviolet light source of 365 nm under nitrogen protection. The reaction temperature is 45 ° C and the reaction time is 1.5 h. After the reaction is completed, centrifuge, wash and dry to obtain modified silica.

[0037] (4) Dissolve 10 g of chitosan in 500 ml of 1.5% v / v acetic acid solution, add 2.0 g of ammonium persulfate, stir evenly, add 28 g of acrylonitrile monomer under nitrogen atmosphere, react at 65 °C for 5 h, after the reaction, pour the reaction mixture into anhydrous ethanol, centrifuge, wash and dry to obtain acrylonitrile grafted chitosan;

[0038] (5) 10 g of acrylonitrile grafted chitosan was dispersed in 200 ml of a methanol / THF mixed solvent. Under ice bath conditions, 6.5 g of sodium borohydride was slowly added in batches. The temperature was raised to 25 °C and the reaction was continued for 2.5 h. After the reaction was completed, 1 mol / L dilute hydrochloric acid was immediately added to adjust the pH of the solution to neutral. The reaction mixture was poured into an excess of deionized water, centrifuged, washed, and dried to obtain modified chitosan.

[0039] (6) Disperse 10 g of modified silica in 100 ml of DMF and disperse by ultrasonic for 30 min. Add 12 g of EDC and 5 g of NHS and activate with stirring at 25 °C for 25 min. Add 16.5 g of modified chitosan, which is prepared into a solution with a mass percentage of 1-2%, and add the solution. React at 25 °C for 20 h. After the reaction is completed, filter, wash and dry to obtain a modified antibacterial filler.

[0040] (7) Weigh 100 g of nitrile rubber modified polylactic acid, 8 g of modified antibacterial filler, 2 g of 2,6-di-tert-butyl-p-cresol, 1.0 g of sulfur, 1.0 g of zinc oxide, 1.3 g of diphenylguanidine and 0.8 g of sodium fluorosilicate, mix the nitrile rubber modified polylactic acid, 2,6-di-tert-butyl-p-cresol and modified antibacterial filler thoroughly, then add sulfur, zinc oxide, diphenylguanidine and sodium fluorosilicate in sequence to ensure that each component is evenly dispersed, adjust the amount of water, and keep the solid content of the impregnation liquid at 30%; preheat a clean and dry hand mold to 50°C, then slowly immerse it in the impregnation latex for 30 seconds, take it out and let it stand at 25°C for 2 minutes, wait for the rubber to form a uniform film on the surface of the hand mold, place the hand mold with the film in a hot air circulation oven, and vulcanize it at 140°C for 15 minutes. After the vulcanization is completed, remove the mold to obtain a degradable, breathable and antibacterial glove.

[0041] Example 2

[0042] This embodiment provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0043] (1) Add 5 g of hexadecyltrimethylammonium bromide to a mixed solution of 10 ml of ammonia water (mass fraction of 25%), 600 ml of deionized water and 400 ml of ethanol, stir evenly at 25°C, then add 5 ml of ethyl orthosilicate and 4 ml of 3-aminopropyltrimethoxysilane, react at 25°C for 4 h, and after the reaction is completed, wash with deionized water and anhydrous ethanol in turn to obtain amino silica; place the amino silica in a crucible and calcine in a muffle furnace at a calcination temperature of 500°C for 6 h. After the calcination is completed, cool to 25°C with the furnace to obtain amino mesoporous silica;

[0044] (2) Disperse 10 g of amino-modified mesoporous silica in 100 ml of THF, and ultrasonically disperse for 30 min. Add 10 g of triethylamine under nitrogen protection and stir evenly. Then, slowly dropwise add 20 g of oleoyl chloride in an ice bath. After the dropwise addition is completed, heat to 50 ° C and continue to stir and react for 8 h. After the reaction is completed, filter, wash and dry to obtain amidated silica.

[0045] (3) Disperse 10 g of amidated silica in 100 ml of DMF, perform ultrasonic dispersion for 30 min, add 15 g of 2-mercaptobenzimidazole carboxylic acid and 2 g of benzophenone, and irradiate the mixture with an ultraviolet light source of 365 nm under nitrogen protection. The reaction temperature is 40 ° C and the reaction time is 2 h. After the reaction is completed, centrifuge, wash and dry to obtain modified silica.

[0046] (4) Dissolve 10 g of chitosan in 500 ml of 1% v / v acetic acid solution, add 0.8 g of ammonium persulfate, stir evenly, add 25 g of acrylonitrile monomer under nitrogen atmosphere, react at 60 °C for 6 h, after the reaction is completed, pour the reaction mixture into anhydrous ethanol, centrifuge, wash and dry to obtain acrylonitrile grafted chitosan;

[0047] (5) 10 g of acrylonitrile grafted chitosan was dispersed in 200 ml of a methanol / THF mixed solvent. 5 g of sodium borohydride was slowly added in batches under ice bath conditions. The temperature was raised to 25 °C and the reaction was continued for 3 h. After the reaction was completed, 1 mol / L dilute hydrochloric acid was immediately added to adjust the pH of the solution to neutral. The reaction mixture was poured into an excess of deionized water, centrifuged, washed, and dried to obtain modified chitosan.

[0048] (6) Disperse 10 g of modified silica in 100 ml of DMF and disperse by ultrasonic for 30 min. Add 12 g of EDC and 5 g of NHS and activate with stirring at 25 °C for 20 min. Add 15 g of modified chitosan, which is prepared into a solution with a mass percentage of 1-2%, and add the solution. React at 25 °C for 16 h. After the reaction is completed, filter, wash and dry to obtain a modified antibacterial filler.

[0049] (7) Weigh 100 g of nitrile rubber modified polylactic acid, 5 g of modified antibacterial filler, 1 g of 2,6-di-tert-butyl-p-cresol, 0.25 g of sulfur, 0.25 g of zinc oxide, 0.3 g of diphenylguanidine and 0.5 g of sodium fluorosilicate, mix the nitrile rubber modified polylactic acid, 2,6-di-tert-butyl-p-cresol and modified antibacterial filler in an internal mixer, then add sulfur, zinc oxide, diphenylguanidine and sodium fluorosilicate in sequence to ensure that the components are evenly dispersed, adjust the amount of water, and keep the solid content of the impregnation liquid at 20%; preheat a clean and dry hand mold to 50°C, then slowly immerse it in the impregnation latex for 30 seconds, take it out and let it stand at 25°C for 2 minutes, wait for the rubber to form a uniform film on the surface of the hand mold, place the hand mold with the film in a hot air circulation oven, and vulcanize it at 130°C for 20 minutes. After the vulcanization is completed, remove the mold to obtain a degradable, breathable and antibacterial glove.

[0050] Example 3

[0051] This embodiment provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0052] (1) Add 10 g of hexadecyltrimethylammonium bromide to a mixed solution of 15 ml of ammonia water (mass fraction of 28%), 800 ml of deionized water and 600 ml of ethanol, stir evenly at 30°C, then add 12 ml of ethyl orthosilicate and 6 ml of 3-aminopropyltrimethoxysilane, react at 30°C for 5 h, and after the reaction is completed, wash with deionized water and anhydrous ethanol in turn to obtain amino silica; place the amino silica in a crucible and calcine in a muffle furnace at a calcination temperature of 550°C for 5 h. After the calcination is completed, cool to 30°C with the furnace to obtain amino mesoporous silica;

[0053] (2) Disperse 10 g of amino-modified mesoporous silica in 100 ml of THF, and ultrasonically disperse for 30 min. Add 10 g of triethylamine under nitrogen protection and stir evenly. Then, slowly dropwise add 30 g of oleoyl chloride under ice bath conditions. After the dropwise addition is complete, heat to 60 ° C and continue to stir and react for 6 h. After the reaction is completed, filter, wash and dry to obtain amidated silica.

[0054] (3) Disperse 10 g of amidated silica in 100 ml of DMF, perform ultrasonic dispersion for 30 min, add 20 g of 2-mercaptobenzimidazole carboxylic acid and 4 g of benzophenone, and irradiate the mixture with an ultraviolet light source of 365 nm under nitrogen protection. The reaction temperature is 50 ° C and the reaction time is 1 h. After the reaction is completed, centrifuge, wash and dry to obtain modified silica.

[0055] (4) Dissolve 10 g of chitosan in 500 ml of 2% v / v acetic acid solution, add 3 g of ammonium persulfate, stir evenly, add 30 g of acrylonitrile monomer under nitrogen atmosphere, react at 70 °C for 4 h, after the reaction is completed, pour the reaction mixture into anhydrous ethanol, centrifuge, wash and dry to obtain acrylonitrile grafted chitosan;

[0056] (5) 10 g of acrylonitrile grafted chitosan was dispersed in 200 ml of a methanol / THF mixed solvent. Under ice bath conditions, 8 g of sodium borohydride was slowly added in batches. The temperature was raised to 25 °C and the reaction was continued for 2 h. After the reaction was completed, 1 mol / L dilute hydrochloric acid was immediately added to adjust the pH of the solution to neutral. The reaction mixture was poured into an excess of deionized water, centrifuged, washed, and dried to obtain modified chitosan.

[0057] (6) Disperse 10 g of modified silica in 100 ml of DMF and disperse by ultrasonic for 30 min. Add 12 g of EDC and 5 g of NHS and activate by stirring at 30 °C for 30 min. Add 18 g of modified chitosan, which is prepared into a solution with a mass percentage of 1-2%, and react at 30 °C for 24 h. After the reaction is completed, filter, wash and dry to obtain a modified antibacterial filler.

[0058] (7) Weigh 100 g of nitrile rubber modified polylactic acid, 10 g of modified antibacterial filler, 3 g of 2,6-di-tert-butyl-p-cresol, 1.5 g of sulfur, 1.5 g of zinc oxide, 2 g of diphenylguanidine and 1 g of sodium fluorosilicate, mix the nitrile rubber modified polylactic acid, 2,6-di-tert-butyl-p-cresol and modified antibacterial filler in an internal mixer, then add sulfur, zinc oxide, diphenylguanidine and sodium fluorosilicate in sequence to ensure that the components are evenly dispersed, adjust the amount of water, and keep the solid content of the impregnation liquid at 40%; preheat a clean and dry hand mold to 50°C, then slowly immerse it in the impregnation latex for 30 seconds, take it out and let it stand at 30°C for 2 minutes, wait for the rubber to form a uniform film on the surface of the hand mold, place the hand mold with the film in a hot air circulation oven, and vulcanize it at 150°C for 10 minutes. After the vulcanization is completed, remove the mold to obtain a degradable, breathable and antibacterial glove.

[0059] Comparative Example 1

[0060] This comparative example provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0061] (1) Add 8 g of hexadecyltrimethylammonium bromide to a mixed solution of 12.5 ml of ammonia water (mass fraction of 26%), 700 ml of deionized water and 500 ml of ethanol, stir evenly at 25°C, then add 8 ml of ethyl orthosilicate and 5 ml of 3-aminopropyltrimethoxysilane, react at 25°C for 4.5 h, and after the reaction is completed, wash with deionized water and anhydrous ethanol in turn to obtain amino silica; place the amino silica in a crucible and calcine in a muffle furnace at a calcination temperature of 520°C for 5.5 h. After the calcination is completed, cool to 25°C with the furnace to obtain amino mesoporous silica;

[0062] (2) Disperse 10 g of amino-modified mesoporous silica in 100 ml of THF, and ultrasonically disperse for 30 min. Add 10 g of triethylamine under nitrogen protection and stir evenly. Then, slowly dropwise add 25 g of oleoyl chloride in an ice bath. After the dropwise addition is completed, heat to 55 °C and continue to stir and react for 7 h. After the reaction is completed, filter, wash and dry to obtain amidated silica.

[0063] (3) Dissolve 10 g of chitosan in 500 ml of 1-2% acetic acid solution (volume fraction), add 2.0 g of ammonium persulfate, stir evenly, add 28 g of acrylonitrile monomer under nitrogen atmosphere, react at 65 °C for 5 h, after the reaction is completed, pour the reaction mixture into anhydrous ethanol, centrifuge, wash, and dry to obtain acrylonitrile grafted chitosan;

[0064] (4) 10 g of acrylonitrile grafted chitosan was dispersed in 200 ml of a methanol / THF mixed solvent. Under ice bath conditions, 6.5 g of sodium borohydride was slowly added in batches. The temperature was raised to 25 °C and the reaction was continued for 2.5 h. After the reaction was completed, 1 mol / L dilute hydrochloric acid was immediately added to adjust the pH of the solution to neutral. The reaction mixture was poured into an excess of deionized water, centrifuged, washed, and dried to obtain modified chitosan.

[0065] (5) Disperse 10 g of amidated silica in 100 ml of DMF and disperse by ultrasonic for 30 min. Add 12 g of EDC and 5 g of NHS and stir and mix at 25 °C for 25 min. Add 16.5 g of modified chitosan, which is prepared into a solution with a mass percentage of 1-2%, and add the solution. Mix at 25 °C for 20 h. Filter, wash and dry to obtain a modified antibacterial filler.

[0066] Step (6) is the same as step (7) in Example 1.

[0067] Comparative Example 2

[0068] This comparative example provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0069] (1) Add 8 g of hexadecyltrimethylammonium bromide to a mixed solution of 12.5 ml of ammonia water (mass fraction of 26%), 700 ml of deionized water and 500 ml of ethanol, stir evenly at 25°C, then add 8 ml of ethyl orthosilicate and 5 ml of 3-aminopropyltrimethoxysilane, react at 25°C for 4.5 h, and after the reaction is completed, wash with deionized water and anhydrous ethanol in turn to obtain amino silica; place the amino silica in a crucible and calcine in a muffle furnace at a calcination temperature of 520°C for 5.5 h. After the calcination is completed, cool to 25°C with the furnace to obtain amino mesoporous silica;

[0070] (2) Disperse 10 g of amino mesoporous silica in 100 ml of THF, and ultrasonically disperse for 30 min. Add 10 g of triethylamine under nitrogen protection and stir evenly. Then, slowly drop 25 g of oleoyl chloride in an ice bath. After the dropwise addition, heat to 55 °C and continue stirring for 7 h. After the reaction, filter, wash and dry to obtain amidated silica.

[0071] (3) Disperse 10 g of amidated silica in 100 ml of DMF, perform ultrasonic dispersion for 30 min, add 18 g of 2-mercaptobenzimidazole carboxylic acid and 3 g of benzophenone, and irradiate the mixture with an ultraviolet light source of 365 nm under nitrogen protection. The reaction temperature is 45 ° C and the reaction time is 1.5 h. After the reaction is completed, centrifuge, wash and dry to obtain modified silica.

[0072] (4) Disperse 10 g of modified silica in 100 ml of DMF and disperse by ultrasonic for 30 min. Add 12 g of EDC and 5 g of NHS and activate with stirring at 25 °C for 25 min. Add 16.5 g of chitosan in a solution with a mass percentage of 1-2% and react at 25 °C for 20 h. After the reaction is completed, filter, wash and dry to obtain a modified antibacterial filler.

[0073] Step (5) is the same as step (7) in Example 1.

[0074] Comparative Example 3

[0075] This comparative example provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0076] Steps (1) to (3) are the same as steps (1) to (3) of Comparative Example 2;

[0077] (4) Dissolve 10 g of chitosan in 500 ml of 1-2% acetic acid solution (volume fraction), add 2.0 g of ammonium persulfate, stir evenly, add 28 g of acrylonitrile monomer under nitrogen atmosphere, react at 65 °C for 5 h, after the reaction, pour the reaction mixture into anhydrous ethanol, centrifuge, wash and dry to obtain acrylonitrile grafted chitosan;

[0078] (5) Disperse 10 g of modified silica in 100 ml of DMF and disperse by ultrasonic for 30 min. Add 12 g of EDC and 5 g of NHS and activate with stirring at 25 °C for 25 min. Add 16.5 g of acrylonitrile grafted chitosan in a solution of 1-2% by mass and add the solution. React at 25 °C for 20 h. After the reaction is completed, filter, wash and dry to obtain a modified antibacterial filler.

[0079] Step (6) is the same as step (5) of Comparative Example 2.

[0080] Comparative Example 4

[0081] This comparative example provides a method for preparing biodegradable breathable antibacterial gloves, comprising the following steps:

[0082] (1) Add 8 g of hexadecyltrimethylammonium bromide to a mixed solution of 12.5 ml of ammonia water (mass fraction 26%), 700 ml of deionized water and 500 ml of ethanol, stir evenly at 25°C, then add 8 ml of ethyl orthosilicate and 5 ml of 3-aminopropyltrimethoxysilane, react at 25°C for 4.5 h. After the reaction is completed, wash with deionized water and anhydrous ethanol in turn to obtain amino silica;

[0083] Steps (2) to (7) are the same as steps (2) to (7) of Example 1.

[0084] Comparative Example 5

[0085] Weigh 100g of nitrile rubber grafted polylactic acid, 3g of 2,6-di-tert-butyl-p-cresol, 1.5g of sulfur, 1.5g of zinc oxide, 2g of diphenylguanidine and 1g of sodium fluorosilicate, mix the nitrile rubber and 2,6-di-tert-butyl-p-cresol evenly in an internal mixer, then add sulfur, zinc oxide, diphenylguanidine and sodium fluorosilicate in sequence to ensure that each component is evenly dispersed, adjust the amount of water, and keep the solid content of the impregnation liquid at 40%; preheat a clean and dry hand mold to 50°C, then slowly immerse it in the impregnation latex, stay for 30s, take it out and let it stand at 25°C for 2min, wait for the rubber to form a uniform film on the surface of the hand mold, place the hand mold with the film in a hot air circulation oven, and vulcanize it at 150°C for 10min. After the vulcanization is completed, remove the mold to obtain a degradable, breathable and antibacterial glove.

[0086] Performance Testing

[0087] The antibacterial performance of the degradable breathable antibacterial gloves prepared in the examples and comparative examples was tested. The antibacterial performance test method was as follows: first, a 2 cm × 2 cm glove sample was sterilized, and then Staphylococcus aureus, Candida albicans, and Escherichia coli were dropped on the surface of the sterile sample, respectively, with a concentration of 10 7 cfu / mL, the amount of bacterial solution added was 0.05mL / cm 2 Then the sample was incubated at 37℃ for 24h, and then the bacterial solution on the sample was diluted in multiple ratios and inoculated on an agar plate containing a culture medium, and incubated in a 37℃ constant temperature incubator for 24h, and the number of live bacteria was calculated (refer to GB / T4789.2); the number of live bacteria was divided by the total number of bacteria to calculate the antibacterial rate; antibacterial persistence: the glove samples were stored at room temperature and ventilated for 60d, and the antibacterial rate during the test period was measured. The results are shown in Table 1.

[0088] Table 1 Antibacterial properties

[0089]

[0090] It can be seen from Table 1 that the biodegradable breathable antibacterial gloves prepared by the technical solution of the present invention have good antibacterial properties, and the antibacterial properties of the gloves can be improved by the synergistic effect of the benzimidazole group and chitosan in the modified antibacterial filler.

[0091] The degradable breathable antibacterial gloves prepared in the examples and comparative examples were tested for air permeability and degradability using an oxygen permeability tester; Degradation performance test: 500g of outdoor natural soil was randomly weighed, crushed and sieved, and 100mL of distilled water was added to dilute and stir into a muddy state to simulate environmental soil, and then 2g of degradable breathable antibacterial gloves were added to the simulated environmental soil, and placed for 30d, 60d, and 90d, respectively, and 5mL of distilled water was added every 10 days, and then the samples were taken out and weighed, and the degradation rate Q was calculated, which was the mass difference before and after degradation / 2g. The test results are shown in Table 2.

[0092] Table 2 Air permeability and biodegradability

[0093]

[0094] It can be seen from Table 2 that the degradable breathable antibacterial gloves prepared by the technical solution of the present invention have good air permeability and degradability.

[0095] The degradable breathable antibacterial gloves prepared in the examples and comparative examples were subjected to mechanical property tests, and the tensile strength and elongation at break of the degradable breathable antibacterial gloves were tested using a universal testing machine. The test results are shown in Table 3.

[0096] Table 3 Mechanical properties

[0097]

[0098] It can be seen from Table 3 that the degradable breathable antibacterial gloves prepared by the technical solution of the present invention still have good mechanical properties.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A degradable breathable antibacterial glove, characterized by: The emulsion formula of the degradable breathable antibacterial gloves is as follows: 100 parts of nitrile rubber modified polylactic acid, 5-10 parts of modified antibacterial filler, 1-3 parts of anti-aging agent, 0.5-3 parts of vulcanizing agent, 0.3-2 parts of vulcanization accelerator and 0.5-1 parts of foaming agent by weight. The preparation method of the modified antibacterial filler is as follows: S1, dispersing the amino mesoporous silica in THF, adding triethylamine and oleyl chloride under nitrogen protection, stirring and reacting to obtain amidated silica; S2, dispersing the amidated silica in DMF, adding 2-mercaptobenzimidazole carboxylic acid and a photoinitiator, and subjecting to ultraviolet irradiation reaction to obtain modified silica; S3, dissolving chitosan in 1-2% v / v acetic acid solution, adding ammonium persulfate, and then adding acrylonitrile monomer to react to obtain acrylonitrile-grafted chitosan; S4, acrylonitrile grafted chitosan was dispersed in a methanol / THF mixed solvent, sodium borohydride was added under ice bath condition, the temperature was raised to 25-30°C and the reaction was continued for 2-3h, and dilute hydrochloric acid was immediately added after the reaction was completed for neutralization to obtain modified chitosan; S5, dispersing the modified silica in DMF, adding EDC and NHS, activating for 20-30 min, adding the modified chitosan solution, reacting at 25-30° C. for 16-24 h, and obtaining a modified antibacterial filler; The preparation method of the amino mesoporous silica is as follows: S11, adding hexadecyltrimethylammonium bromide to a mixed solution of ammonia water, deionized water and ethanol, stirring evenly, then adding tetraethyl orthosilicate and aminosilane coupling agent, reacting for 4-5h, to obtain amino silica; S12. Place the amino-containing silica in a crucible and calcine in a muffle furnace at a temperature of 500-550° C. for 5-6 hours to obtain amino-containing mesoporous silica.

2. The degradable breathable antibacterial glove according to claim 1, characterized in that: In step S11, the mass volume ratio of hexadecyltrimethylammonium bromide, ammonia water, deionized water, anhydrous ethanol, ethyl orthosilicate and aminosilane coupling agent is 0.5-1.0g:1-1.5ml:60-80ml:40-60ml:0.5-1.2ml:0.4-0.6ml, and the aminosilane coupling agent is 3-aminopropyltrimethoxysilane or 3-aminopropyltriethoxysilane.

3. The degradable breathable antibacterial glove according to claim 1, characterized in that: In step S1, the mass ratio of amino silicon dioxide, oleoyl chloride and triethylamine is 1:2-3:1, the reaction temperature is 50-60° C., and the reaction time is 6-8 h.

4. The degradable breathable antibacterial glove according to claim 1, characterized in that: In step S2, the mass ratio of amidated silica, 2-mercaptobenzimidazole carboxylic acid and photoinitiator is 1:1.5-2:0.2-0.4, the reaction temperature is 40-50°C, and the reaction time is 1-2h; the photoinitiator is diphenylacetone.

5. The degradable breathable antibacterial glove according to claim 1, characterized in that: In step S3, the mass ratio of chitosan to acrylonitrile is 1:2.5-3, the amount of ammonium persulfate added is 2-5% of the total mass of chitosan and acrylonitrile; the reaction temperature is 60-70° C., and the reaction time is 4-6 hours.

6. The degradable breathable antibacterial glove according to claim 1, characterized in that: In step S4, the mass ratio of acrylonitrile grafted chitosan and sodium borohydride is 1:0.5-0.8; in step S5, the mass ratio of modified silica, modified chitosan, EDC and NHS is 1:1.5-1.8:1.2:0.5, and the mass percentage of chitosan in the modified chitosan solution is 1-2%.

7. The degradable breathable antibacterial glove according to claim 1, characterized in that: The anti-aging agent is 2,6-di-tert-butyl-p-cresol, the vulcanizing agent is sulfur and zinc oxide, the vulcanization accelerator is any one or more of diphenylguanidine, diethylthiourea, thiuram and 2-mercaptobenzothiazole, and the foaming agent is sodium fluorosilicate.

8. A method for preparing a degradable breathable antibacterial glove according to any one of claims 1 to 7, characterized in that: The following steps are involved: The dipping latex is prepared according to the emulsion formula of the degradable breathable antibacterial gloves, and the amount of water is adjusted to keep the solid content of the dipping liquid at 20-40%. The hand mold is dipped in the dipping latex, and the degradable breathable antibacterial gloves are obtained through heating, vulcanization and demoulding.

Citation Information

Patent Citations

  • Antibacterial PLA-based degradable polymer material, preparation method and application of antibacterial PLA-based degradable polymer material in emulsion pump head

    CN117777692A

  • Antimicrobial silcone rubber, preparation method therefor and use thereof

    US20200017651A1